Involvement of formyl peptide receptors in receptor for advanced glycation end products (RAGE) - and amyloid beta 1-42-induced signal transduction in glial cells - Slowik Alexander; Merres Julika; Elfgen Anne; Jansen Sandra; Mohr Fabian; Wruck Christoph J; Pufe Thomas; Brandenburg Lars-Ove (Molecular Neurodegeneration, 2012)
Abstract Background Recent studies suggest that the chemotactic G-protein-coupled-receptor (GPCR) formyl-peptide-receptor-like-1 (FPRL1) and the receptor-for-advanced-glycation-end-products (RAGE) play an important role in the inflammatory response involved in neurodegenerative disorders such as Alzheimer’s disease (AD). Therefore, the expression and co-localisation of mouse formyl peptide receptor (mFPR) 1 and 2 as well as RAGE in an APP/PS1 transgenic mouse model using immunofluorescence and real-time RT-PCR were analysed. The involvement of rat or human FPR1/FPRL1 (corresponds to mFPR1/2) and RAGE in amyloid-β 1–42 (Aβ1-42)-induced signalling were investigated by extracellular signal regulated kinase 1/2 (ERK1/2) phosphorylation. Furthermore, the cAMP level in primary rat glial cells (microglia and astrocytes) and transfected HEK 293 cells was measured. Formyl peptide receptors and RAGE were inhibited by a small synthetic antagonist WRW4 and an inactive receptor variant delta-RAGE, lacking the intracytoplasmatic domains. Results We demonstrated a strong increase of mFPR1/2 and RAGE expression in the cortex and hippocampus of APP/PS1 transgenic mice co-localised to the glial cells. In addition, the Aβ1-42-induced signal transduction is dependant on FPRL1, but also on FPR1. For the first time, we have shown a functional interaction between FPRL1/FPR1 and RAGE in RAGE ligands S100B- or AGE-mediated signalling by ERK1/2 phosphorylation and cAMP level measurement. In addition a possible physical interaction between FPRL1 as well as FPR1 and RAGE was shown with co-immunoprecipitation and fluorescence microscopy. Conclusions The results suggest that both formyl peptide receptors play an essential role in Aβ1-42-induced signal transduction in glial cells. The interaction with RAGE could explain the broad ligand spectrum of formyl peptide receptors and their important role for inflammation and the host defence against infections.